Prevalence of strongyloidiasis among cardiothoracic organ transplant candidates in a non‐endemic region: A single‐center experience with universal screening. Issue 4 (24th April 2021) - Kottkamp, Angelica C.; Filardo, Thomas D.; Holzman, Robert S.; Aguero‐Rosenfeld, Maria; Neumann, Henry J.; Mehta, Sapna A.
Abstract: Disseminated strongyloidiasis and hyperinfection syndrome can cause significant morbidity and mortality after transplantation. Screening and treatment prior to transplantation can reduce or prevent this disease. Targeted screening of transplant candidates based on assessed risk, fails to identify all who would benefit. We implemented universal serology‐based screening for Strongyloides at our transplant center, located in a non‐endemic area. Of 200 transplant candidates who were evaluated for cardiothoracic transplant from January 2018 to June 2019, 169 were screened serologically and 21 (12.4%) were seropositive. Among seropositive patients, 57% reported travel to an endemic region, 38% were born outside the USA, 38% had eosinophilia, and 5% had history of gram‐negative bacteremia. We estimate that universal screening for strongyloidiasis could identify an average of 17 additional candidates for preventive treatment for every 200 transplant candidates.